2021
DOI: 10.15562/bmj.v10i2.2524
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor (EGF) representing the role of other growth factors contained in Platelet-Rich Plasma (PRP)

Abstract: Background: Wound care with modern dressings that have been widely used takes time to achieve healing. Therefore, Epidermal Growth Factor (EGF) and Platelet-Rich Plasma (PRP) are developed in wound healing therapy. EGF as the primary growth factor examines whether it is sufficient to represent the role of other growth factors in PRP. EGF is also chosen because of its ease of provision and longer shelf life compared to PRP. This study evaluates the (EGF) representing the role of other growth factors contained i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…These results indicated that the scaffolds were effectively incorporated into wounds. The closure was accomplished via re-epithelialization by keratinocytes in endogenous wounds [ 48 ] since EGFR significantly enhances the rate of macroscopic healing in PRP-treated tissue compared to control wounds.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that the scaffolds were effectively incorporated into wounds. The closure was accomplished via re-epithelialization by keratinocytes in endogenous wounds [ 48 ] since EGFR significantly enhances the rate of macroscopic healing in PRP-treated tissue compared to control wounds.…”
Section: Discussionmentioning
confidence: 99%
“…th day. This is because the wound that has undergone epithelial closure or the wound on the subject indicates that the proliferative phase has begun and the remodeling phase has begun [23], [26]. Epithelialization through the wound margin occurs early in the inflammatory phase and rapidly at the end of the proliferative phase [27].…”
Section: Discussionmentioning
confidence: 99%
“…These results showed that the scaffolds were successfully integrated into wounds. The closure was achieved through re-epithelialization by endogenous wound keratinocytes (Nurmaulinda et al 2021 ), as EGFR greatly increases the speed of macroscopic healing in tissue treated with PRP than in control wounds. Additionally, cell quantification immunostained for TGFβ demonstrated ABP contribution as a source of TGF in promoting angiogenesis, epithelial cell proliferation, and the organization of wound sites, as referred by (Wasterlain et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%